Effects of Continuous Erector Spinae Plane Block on the Postoperative Sleep Quality for Patients Undergoing Thoracoscopic Lung Lobe Resection Surgery: A Prospective, Randomized Controlled Trial - Zhang Q; Lu X; Zhang W; Zhong Z; Wang L; Qiao Y; Ling F; Qiu X; Zhang Y (Nature and Science of Sleep)
Qian Zhang,1,2,* Xian Lu,3,* Wen Zhang,4,* Zhenyu Zhong,5,* Lili Wang,4 Yuhan Qiao,4 Fei Ling,4 Xinyuan Qiu,4 Yueying Zhang1,2 1Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of China; 2Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, People’s Republic of China; 3Shanghai Key Laboratory of Psychotic Disorders, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 4Xuzhou Medical University, Xuzhou, People’s Republic of China; 5Department of Anesthesiology, The First Affiliated Hospital of Ningbo University, Ningbo, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yueying Zhang, Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of China, Email zyy0218@126.comPurpose: To investigate the effect of continuous erector spinae plane block (ESPB) on postoperative sleep in patients undergoing thoracoscopic lung lobe resection surgery.Patients and Methods: Eighty-six patients were randomly assigned into two groups: ESPB group (Group E) or control group (Group P). Group E received ESPB before induction, followed by continuous ESPB analgesia, while Group P received postoperative intravenous controlled analgesia. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was used to assess postoperative sleep disturbance (PSD) on the postoperative day 3 (POD3). The St. Mary’s Hospital Sleep Questionnaire (SMH) evaluated sleep quality on the day of surgery and postoperative day 1 (POD1) and postoperative day 2 (POD2). The Identity Consequence Fatigue Scale-10 (ICFS-10) was utilized to evaluate postoperative fatigue status. Numeric Rating Scale (NRS) scores at resting and coughing were recorded at extubation, 6 h, 24 h, 48 h, 72 h after surgery. Consumption of propofol, remifentanil, and remedial analgesics (bucinazine), hospital duration, occurrence of postoperative adverse reactions were documented. Interleukin-6 (IL-6) and interleukin-10 (IL-10) serum levels were measured before surgery, 12 h, 24 h, 48 h after surgery.Results: The incidence of PSD in group E on POD3 was significantly lower than group P (75% vs 25%). Patients in group E had higher SMH scores than group P on the day of surgery and POD2. Compared with group P, the NRS scores of resting and coughing at all time points, remifentanil and bucinazine consumption, postoperative ICFS-10 scores, the incidence of nausea and vomiting, IL-6 serum levels in group E were significantly decreased. The IL-10 serum levels in group E were significantly higher than those in group P.Conclusion: The continuous ESPB can improve postoperative sleep quality, alleviate pain, fatigue and inflammation, and reduce the incidence of postoperative nausea and vomiting.Keywords: continuous erector spinae plane block, thoracoscopic, lung lobe resection, postoperative sleep disturbance